The Impact of Intravascular Imaging (IVUS/OCT) Guidance on Preventing In-Stent Restenosis and Improving Long-Term Clinical Outcomes in Complex PCI: A Meta-Analysis - Lian Lanrika Waidi Lubis; Taufik Indrajaya; Ferry Usnizar; Erwin Sukandi; Syamsu Indra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Percutaneous coronary intervention (PCI) in patients with complex coronary artery disease is associated with a higher risk of adverse events, including in-stent restenosis (ISR). Intravascular imaging, using either intravascular ultrasound (IVUS) or optical coherence tomography (OCT), has been proposed to optimize stent implantation and improve outcomes, but its definitive role requires comprehensive evidence synthesis. Methods: We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs). Major electronic databases (PubMed, EMBASE, Cochrane CENTRAL) were searched from January 2014 to May 2025 for RCTs comparing intravascular imaging-guided PCI with angiography-guided PCI in patients undergoing complex procedures. The primary efficacy endpoint was Major Adverse Cardiovascular Events (MACE), a composite of cardiac death, target-vessel myocardial infarction, and clinically-driven target lesion revascularization. The key secondary endpoint was angiographic ISR. A random-effects model was used to calculate pooled Risk Ratios (RRs) and 95% Confidence Intervals (CIs). Results: Seven RCTs, enrolling a total of 9,150 patients, met the inclusion criteria. The median follow-up was 24 months. Intravascular imaging guidance was associated with a significant reduction in the risk of MACE (RR: 0.66; 95% CI: 0.55-0.79; p<0.0001) compared to angiography guidance, with moderate heterogeneity (I²=52%). The risk of angiographic ISR was also significantly lower in the imaging-guided group (RR: 0.49; 95% CI: 0.38-0.63; p<0.0001). Furthermore, imaging guidance led to a significant reduction in cardiac death (RR: 0.55; 95% CI: 0.38-0.80) and clinically-driven target lesion revascularization (RR: 0.54; 95% CI: 0.42-0.69). Conclusion: This meta-analysis provides definitive evidence that the use of intravascular imaging (IVUS or OCT) to guide complex PCI significantly reduces the incidence of long-term major adverse cardiovascular events and in-stent restenosis. These findings support the routine adoption of intravascular imaging as the standard of care to optimize outcomes in this high-risk patient population.